Determinants of Financial Literature as Investment Decisions (Case Study on PT Bank Rakyat Indonesia's Employees, Tbk) Employees - Rizqi Amalia Yasinta Putri; Wisnu Mawardi (Budapest International Research and Critics University, 2022)
Financial literacy education is needed so that the public can optimize financial management through existing financial products and services that are appropriate and to their needs. This type of research is descriptive and quantitative. In this study, the research subjects were BRI employees. At the same time, the research object is the level of financial literacy and investment decisions. In this study, the analytical technique used is Partial Least Square (PLS). This study aimed to determine the effect of age, culture, gender, and education on investment decisions. To determine the effect of age, culture, gender, and education on financial literacy and financial literacy's effect on investment decisions. The results showed that the higher the score on financial literacy affects stock investment decisions, the more financial literacy positively influences investment decisions. Meanwhile, age, culture, gender, and education do not affect investment decisions. Improving investment decisions can be done by increasing financial literacy.